The Outdoor Sports Facilities at the Education Park of Faculty of Teacher and Education Sriwijawa University - Hartati; Iyakrus; Meirizal Usra (Universitas Negeri Semarang, 2024)
The importance of physical fitness cannot be overstated as it is essential for daily activities and overall well-being. Sports science contributes significantly to this field by advancing training methods, managing competition effectively, and utilizing advanced instruments to measure athletic ability. These developments in sports science play an important role in optimizing performance and achieving fitness goals. This research aims to provide facilities and infrastructure as well as sports facilities that function as important infrastructure in supporting the success of sports education and facilitating student achievement and as an effective tool for assessing the physical fitness of Physical Education students and the wider university community. This research uses a quantitative descriptive approach with a focus on Physical Education students in 2022 as respondents. Research results: This facility is specifically designed to carry out various physical fitness tests for students, lecturers and staff, providing a structured environment to assess and improve fitness levels at the Faculty of Teacher Training and Education, Sriwijawa University to lead a healthier life. In conclusion, the integration of physical education, sports science, and dedicated sports facilities underscores a comprehensive approach to fostering physical fitness, skill development, and overall well-being among students and university members at the Faculty of Teacher Training and Education, Sriwijawa University.